Using intelligent agents to understand organisational behaviour - Celia, Helen; Clegg, Christopher; Robinson, Mark; Siebers, Peer-Olaf; Aickelin, Uwe; Sprigg, Christine (2007)
This paper introduces two ongoing research projects which seek to apply computer modelling techniques in order to simulate human behaviour within organisations. Previous research in other disciplines has suggested that complex social behaviours are governed by relatively simple rules which, when identified, can be used to accurately model such processes using computer technology. The broad objective of our research is to develop a similar capability within organisational psychology.